Fe-doped MoS2 nanomaterials with amplified peroxidase mimetic activity for the colorimetric detection of glutathione in human serum - Singh P.; Ojha R.P.; Kumar S.; Singh A.K.; Prakash R. (My University, 2025)
In this paper, transition metal-doped MoS2 2D materials have been explored for the colorimetric detection of glutathione based on peroxidase mimetic activity. We have synthesized (hydrothermal) and characterized various doped MoS2. Among them, Fe-doped MoS2 flowers exhibit excellent peroxidase-mimetic activity over MoS2 by inducing the oxidation of chromogenic substrate and results in a blue color charge transfer product. Property of this nanomaterial is exploited for efficacious detection of Glutathione level in the buffer as well as in serum samples which follows the steady-state kinetics for peroxidase mimetic activity and exhibits stability over harsh environmental conditions. The developed sensor shows good linearity for glutathione detection in the range 1–30 μM with a significant limit of detection (0.577 μM). The Fe-doped MoS2 with excellent mimetic activity is utilized to develop noble-metal free, high-performance, low-cost peroxidase mimetic activity for onsite detection of glutathione in the real sample. © 2021 Elsevier B.V.